A Randomized Controlled Trial for Prevention of Postoperative Nausea and Vomiting after Laparoscopic Sleeve Gastrectomy: Aprepitant/Dexamethasone vs. Mirtazapine/Dexamethasone. (30th April 2022) - Ashoor, Tarek M.; Kassim, Dina Y.; Esmat, Ibrahim M.
Abstract : Background . Coadministration of different antiemetics proved to decrease postoperative nausea and vomiting (PONV) after laparoscopic sleeve gastrectomy (LSG). This trial compared aprepitant/dexamethasone (A/D) combination vs mirtazapine/dexamethasone (M/D) combination vs dexamethasone ( D ) alone for prevention of PONV in morbidly obese patients undergoing LSG. Methods . Ninety patients scheduled for LSG were randomly allocated to receive 8 mg dexamethasone intravenous infusion (IVI) only in the D group or in addition to 80 mg aprepitant capsule in the A/D group or in addition to 30 mg mirtazapine tablet in the M/D group. Assessment of PONV was carried out at 0–2 h (early) and 2–24 h (late). The primary outcome was the complete response 0‐24 h after surgery. Collective PONV, postoperative pain, side effects and patient satisfaction score were considered as secondary outcomes. Results . The A/D and M/D groups were superior to the D group for a complete response within 0–24 h after surgery (79.3% for the A/D group, 78.6% for the M/D group, and 20.7% for the D group). The D group was inferior to the A/D and M/D groups regarding collective PONV and use of rescue antiemetic 0–24 h after surgery (P < 0.001, P < 0.001, respectively). The peak nausea scores (2–24 h) were significantly reduced in the M/D group in comparison to the D group (P = 0.005 ). Patients in the M/D group showed high sedation scores, while those in the A/D group showed low pain scores (2–24 h) and less analgesic requirements (P < 0.001, P < 0.001, P < 0.001, respectively). The A/D and M/D groups were superior to the D group with regard to the patient satisfaction score (P < 0.001 ). Conclusion . Aprepitant/dexamethasone combination and mirtazapine/dexamethasone combination were superior to dexamethasone alone in alleviating postoperative nausea and vomiting in morbidly obese patients scheduled to undergo laparoscopic sleeve gastrectomy. Trial Registration: ClinicalTrials.gov identifier: NCT04013386 .